Mothering Sunday [large type] : a romance - Swift, Graham, 1949- (Center Point Large Print, 2016)
"At an English country estate in 1924, an afternoon tryst between Jane, a neighboring servant girl, and Paul, the young man of the estate, marks the end of a secret love affair of about six years. Jane's narrative moves back and forth from 1924 to the end of the century to reveal a remarkable woman"--